Laparoscopic vs. open adrenalectomy: perioperative data and survival analysis in 70 dogs with an adrenal tumor - van Bokhorst, Kirsten L.; Galac, Sara; Kooistra, Hans S.; de Grauw, Janny C.; Teske, Erik; Grinwis, Guy C. M.; van Nimwegen, Sebastiaan A. (Frontiers in Veterinary Science, 2023)
Adrenalectomy is the treatment of choice in case of functional adrenal tumors and malignant adrenal incidentalomas. Laparoscopic adrenalectomy (LA) in dogs has gained popularity in recent years, however, clinical studies on large patient populations are scarce. This retrospective study describes perioperative and recurrence data, survival, and prognostic factors in 70 dogs that underwent LA or open adrenalectomy (OA) in our hospital between 2008 and 2022. Diagnosis was based on history, clinical signs, endocrine function tests and advanced diagnostic imaging. Laparoscopic adrenalectomy was performed in 42 dogs (n = 27 naturally occurring hypercortisolism, n = 4 pheochromocytoma, n = 1 pheochromocytoma with concurrent hypercortisolism, n = 10 incidentaloma) and OA in 28 dogs (n = 22 hypercortisolism, n = 3 pheochromocytoma, n = 3 incidentaloma). Bilateral adrenalectomy was performed in 8/70 dogs. Surgical duration of LA and OA did not differ significantly in unilateral and bilateral procedures (P = 0.108 and P = 0.101, respectively). Systemic hypertension occurred in 7/41 and 1/28 dogs during LA and OA, respectively (P = 0.130). Hypotension occurred in 2/41 and 4/28 dogs during LA and OA, respectively (P = 0.214). A total of 40/42 dogs in the LA group and 27/28 in the OA group survived to discharge (P = 0.810). Mean hospital stay was significantly shorter (P = 0.006) after LA (1.5 days, range 1-3) than after OA (2.2 days, range 1-4). No significant differences were demonstrated between LA and OA groups in recurrence of adrenal-dependent endocrine disease (P = 0.332), disease-free period (P = 0.733) and survival time (P = 0.353). The disease-specific 1-, 2- and 3-year survival rates were 95%, 89% and 89% after LA and 92%, 88% and 81% after OA. Tumor size was significantly associated with the occurrence of a recurrence. In addition, tumor size had a negative effect on the disease-free period and survival time. This study shows a favorable outcome of both LA and OA in dogs. Based on low perioperative complication rate, short hospitalization time and long-term outcomes comparable to OA in selected cases, the less invasive laparoscopic approach is considered the preferred technique.